Barriers and enablers of the prevention of mother-to-child transmission of HIV/AIDS program in China: a systematic review and policy implications. (February 2017) - Peng, Zhuoxin; Wang, Shengnan; Xu, Biao; Wang, Weibing
Highlights: Government-oriented multi-sector cooperation is the cornerstone of the prevention of mother-to-child transmission (PMTCT) in China. Barriers in China are at the level of society, the health system, and service recipients and providers. The enablers in China are focused on the acceptability and accessibility of PMTCT. Summary: Objective: To identify the barriers to and enablers of the prevention of mother-to-child transmission (PMTCT) of HIV program in China. Methods: A systematic review of the existing literature regarding barriers to and enablers of the implementation of the PMTCT program in China was performed. The checklist from the SURE guidelines (Supporting the Use of Research Evidence) was used to synthesize the barriers and enablers (supporting strategies) and to analyze their relationships. The HIV testing rate, vertical transmission rate, and antiretroviral treatment (ART) acceptance rate among HIV-infected women and their infants was also extracted from the included studies to assess the effectiveness of the enablers. Results: Initially 794 publications were identified, and ultimately 14 articles were included. Eighteen types of barrier and nine types of supportive strategy were identified, mainly at the level of social and political issues, healthcare recipients, healthcare providers, and the healthcare system. Based on government-oriented multi-sector cooperation, enablers in China have included community–hospital–family promotion, comprehensive financial support for service recipients, free HIV testing at marriage registration, the opt-out model, and the one-to-one service model. Conclusions: Experience in China suggests that the government's role in coordination and the acceptability and accessibility of the service should be the primary concerns in regard to the PMTCT project.